Pengaruh Efikasi Diri, Dukungan Sosial, dan Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha Pada Mahasiswa Manajemen Angkatan 2021 Universitas Jember - Dita Fauziah Nugraheni (Fakultas Ekonomi dan Bisnis, 2025)
University of Jember. The population of this study were undergraduate students of Management University of Jember as many as 187 students with non probability sampling method with census technique on saturated sample with a sample of 147 respondents. The type of data used is quantitative data. The data sources used are primary data obtained from questionnaire results and secondary data obtained from journals, books, official websites of the required data. The data analysis method used is multiple linear regression analysis with SPSS software. The results obtained from the research are self-efficacy has a significant positive effect on entrepreneurial intentions in Management Students in the Class of 2021, University of Jember; social support has a significant negative effect on entrepreneurial intentions in Management Students in the Class of 2021, University of Jember; and entrepreneurship education has a significant positive effect on entrepreneurial intentions in Management Students in the Class of 2021, University of Jember.
Reaploud Repository February_Hasyim
Keywords: entrepreneurship; self-efficacy; social support; entrepreneurship education; entrepreneurial intention